Solving climate change : a guide for learners and leaders - Koomey, Jon; Monroe, Ian (Expert on sustainabiity) (IOP (Series). Release 22., 2022)
This book frames the climate problem in a comprehensive way and cuts through common conceptual confusions that impede rapid action.